Association between Non-Cigarette/Smokeless Tobacco and Hypertension in the National Health Interview Survey: A Pseudo-Panel Analysis - Olawunmi Obisesan; Emmanuel Thompson; Adekunle Obisesan; Olubusayo Akinola; Yvonne Commodore-Mensah (International Journal of Public Health Science (IJPHS), 2016)
This study sought to examine assumption between having ever used non-cigarette tobacco or smokeless tobacco, and a diagnosis of hypertension among a sample of 13, 086 United States adults participating in the National Health Interview Series from 2012-2014. A pseudo-panel analysis of data extracted from the Integrated Health Interview Series Survey was conducted. The generalized linear mixed model was used to quantify the effect of a history of non-cigarette tobacco, smokeless tobacco, and socio-demographic predictor variables on the response variable, a diagnosis of hypertension. The transformed data, based on the pseudo-panel technique, resulted in fifty-seven (57) birth cohorts and followed in 2012, 2013, and 2014. The mean age was 51.6 years (±12.4). The findings of this study revealed that the odds of hypertension diagnosis for non-cigarette tobacco users was 0.8846 times lower (95% CI: 0.7907, 0.9896) than non-users after adjusting for possible confounders such as age, language, education, income and years of smoking. Our study suggested that the association between the use of non-cigarette tobacco and the diagnosis of hypertension among the sample population is consistent enough to assume a less plausible association between the two variables.